Refleksi Teologis Solidaritas Menurut Mgr. Johannes Pujasumarta dalam Terang Ajaran Sosial Gereja - Yohanes Yayan Riawan (Jurnal Teologi (Journal of Theology), 2021)
Solidarity is a process of partiality of the attitudes and views of the Church, namely care for those who are weak and poor and excluded from the formulation of preferential options for the poor. Solidarity have to return to the gospel, learn from Jesus himself who proclaimed God's Kingdom, is present and involved in the world. In solidarity man finds God, the Creator, in his fellow creatures and nature. Solidarity finally changes people in three ways, namely the perception of God, the praxis of life, and the life of prayer which all lead to one and the same thing that is God The Creator who has saved all creation. Solidarity must be manifested in the praxis of daily life in favor of the poor and oppressed.